Therapeutic role of interleukin-1 receptor antagonist in pancreatic diseases: mendelian randomization study - Yuan, Shuai; Miao, Yuyang; Ruan, Xixian; Chen, Jie; Li, Xue; Larsson, Susanna C. (Frontiers in Immunology, 2023)
The interleukin-1 pathway has been linked to pancreatic diseases. We applied the Mendelian randomization approach to explore whether higher interleukin-1 receptor antagonist (IL-1RA) levels reduce the risk of acute and chronic pancreatitis and pancreatic cancer.Methods Genetic variants associated with blood IL-1RA levels at the genome-wide significance level and located 5MB downstream or upstream of the IL1RN gene were extracted from a genome-wide meta-analysis of 21,758 participants. After pruning, genetic variants without linkage disequilibrium were used as genetic instrument for IL-1RA. Summary-level data on acute and chronic pancreatitis and pancreatic cancer were obtained from the UK Biobank and FinnGen studies. The associations were meta-analyzed for one outcome from two sources.Genetically predicted higher levels of IL-1RA were associated with a lower risk of acute and chronic pancreatitis and pancreatic cancer. In the meta-analysis of UK Biobank and FinnGen, the combined odds ratio was 0.87 (95% confidence interval [CI] 0.77-0.97, P=0.003) for acute pancreatitis, 0.73 (95% CI 0.65-0.82, P=2.93×10 -8 ) for chronic pancreatitis, and 0.86 (95% CI 0.77-0.96, P=0.009) for pancreatic cancer per one standard deviation increment in genetically predicted levels of IL-1RA.This study suggests a protective role of IL-1RA in three major pancreatic diseases, which hints the therapeutic potentials of IL-1RA in pancreatic diseases.